LITERATURE REVIEW CUSTOMER SATISFACTION DETERMINATION AND LEVEL OF COMPLAINT: PRODUCT QUALITY AND SERVICE QUALITY - Indra Wibowo, Yusuf (Dinasti International Journal of Digital Business Management, 2022)
Previous research or relevant research is very important in a scientific research or article. Previous research or relevant research serves to strengthen the theory and influence of relationships or influences between variables. Article ini review customer satisfaction determination and complaint level: Product Quality and Service Quality Analysis, A Study of Marketing Management Literature. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The result of this risearch library is that: 1) Product Quality affects Customer Satisfaction; 2) Service Quality affects Customer Satisfaction; 3) Product Quality affects complaint level; 4) Service Quality affects complaint level; and 5) Customer Satisfaction affects complaint level.